Beware of delayed severe brain swelling after intracerebral haematoma in HELLP syndrome - Gioffrè, G (Obstet Med, 2017)
Haemolysis, elevated liver enzymes and low platelets (HELLP) syndrome is a condition associated with increased risk of adverse outcomes during pregnancy and peripartum, including neurological complications. We report the third case in the world literature of delayed brain swelling following cerebral haemorrhage as a complication of HELLP syndrome. A 36-year-old woman in labour developed HELLP, which was complicated with intracerebral haematoma. This was evacuated, but motor impairment persisted after surgery and unfortunately the patient died unexpectedly during the 11th postoperative day. Computer tomographic brain scans documented diffuse cerebral swelling, which we think may have been caused by cerebral vasospasm. Cerebral vasospasm should always be considered when managing patients who suffered from stroke complicating HELLP syndrome. Close monitoring is advised even in later stages of recovery.